Age, growth, and age at sexual maturity of the commercially landed skate species, Dipturus chinensis (Basilewsky, 1855), in the northern East China Sea. (1st December 2017) - Hara, K.; Furumitsu, K.; Aoshima, T.; Kanehara, H.; Yamaguchi, A.
Summary: Age, growth, and age at sexual maturity of the polkadot skate Dipturus chinensis, in the northern East China Sea were determined for a total of 614 specimens collected from April 2009 to December 2014. Vertebral centrum analysis was used to calculate the age of the skates. Annual band deposition was determined by marginal increment analysis. The von Bertalanffy growth model was fitted to the observed length‐at‐age data for each sex (males, L ∞  = 76.8, k  = 0.109, t 0  = −1.28; females, L ∞  = 83.1, k  = 0.103, t 0  = −1.20). Growth patterns of females and males were similar until the age of 6; thereafter, females grew larger than males. Maximum age recorded was 13 years for males and 15 years for females. Age at 50% sexual maturity was 8.22 years for males and 9.39 years for females. These results indicate that D .  chinensis is slow growing, relatively long‐lived, and late maturing, and therefore vulnerable to exploitation.